Beneficial effects of troxerutin on metabolic disorders in non-obese model of metabolic syndrome - Malinska, Hana; Hüttl, Martina; Oliyarnyk, Olena; Markova, Irena; Poruba, Martin; Racova, Zuzana; Kazdova, Ludmila; Vecera, Rostislav (PloS one, 2019)
BACKGROUND: Troxerutin (TRX) has a beneficial effect on blood viscosity and platelet aggregation, and is currently used for the treatment of chronic varicosity. Recently, TRX can improve lipid abnormalities, glucose intolerance and oxidative stress in high-fat diet-induced metabolic disorders. In this study, we tested the effect of TRX on metabolic syndrome-associated disorders using a non-obese model of metabolic syndrome-the Hereditary Hypertriglyceridaemic rats (HHTg). METHODS: Adult male HHTg rats were fed standard diet without or with TRX (150 mg/kg bwt/day for 4 weeks). RESULTS: Compared to untreated rats, TRX supplementation in HHTg rats decreased serum glucose (p<0.05) and insulin (p<0.05). Although blood lipids were not affected, TRX decreased hepatic cholesterol concentrations (p<0.01) and reduced gene expression of HMGCR, SREBP2 and SCD1 (p<0.01), involved in cholesterol synthesis and lipid homeostasis. TRX-treated rats exhibited decreased lipoperoxidation and increased activity of antioxidant enzymes SOD and GPx (p<0.05) in the liver. In addition, TRX supplementation increased insulin sensitivity in muscles and epididymal adipose tissue (p<0.05). Elevated serum adiponectin (p<0.05) and decreased muscle triglyceride (p<0.05) helped improve insulin sensitivity. Among the beneficial effects of TRX were changes to cytochrome P450 family enzymes. Hepatic gene expression of CYP4A1, CYP4A3 and CYP5A1 (p<0.01) decreased, while there was a marked elevation in gene expression of CYP1A1 (p<0.01). CONCLUSION: Our results indicate that TRX improves hepatic lipid metabolism and insulin sensitivity in peripheral tissues. As well as ameliorating oxidative stress, TRX can reduce ectopic lipid deposition, affect genes involved in lipid metabolism, and influence the activity of CYP family enzymes.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; Glycogen; glukosa; Rats; Real-Time Polymerase Chain Reaction; Metabolic Syndrome; transkriptom; Disease Models, Animal; mužské pohlaví; Hydroxyethylrutoside; Muscle, Skeletal; Oxidative Stress; Transcriptome; krysa rodu Rattus; kvantitativní polymerázová řetězová reakce; glykogen; Lipid Metabolism; modely nemocí na zvířatech; zvířata; metabolický syndrom; kosterní svaly; metabolismus lipidů; hypolipidemika; hydroxyethylrutosid; Hypolipidemic Agents; oxidační stres; inzulinová rezistence; Insulin Resistance; Glucose; Male; Animals